Investigation of Adolescent Pregnancy Outcomes and Postpartum Depression Frequency and Risk Factors: Prospective Case Control Study - Mehmet Sukru Budak; Sedat Akgol (Gynecology Obstetrics & Reproductive Medicine)
Objective: The aim of this study was to evaluate the frequency of postpartum depression (PPD), accompanying risk factors, and obstetrics and neonatal outcomes in adolescent pregnancies.